Narrowband UVB Phototherapy for Clinically Isolated Syndrome: A Trial to Deliver the Benefits of Vitamin D and Other UVB-Induced Molecules - Hart, Prue H.; Lucas, Robyn M.; Booth, David R.; Carroll, William M.; Nolan, David; Cole, Judith M.; Jones, Anderson P.; Kermode, Allan G. (Frontiers in Immunology, 2017)
Low vitamin D and insufficient sun exposure are additive independent risk factors for the development of multiple sclerosis (MS). The usual measure of vitamin D status, serum 25-hydroxy vitamin D (25(OH)D), is also a marker of recent exposure to the UVB rays of sunshine. The main evidence for a protective effect for MS development of higher 25(OH)D comes from observational studies, but this study design cannot separate out whether 25(OH)D is acting as a marker of vitamin D status, sun exposure or both. In light of a lack of definitive outcomes in MS patients after trials of vitamin D supplementation and the ability of narrowband UVB to induce vitamin D, as well as other immune-regulatory molecules in skin, the PhoCIS trial (Phototherapy for Clinically Isolated Syndrome) was established to investigate the benefits of narrowband UVB, in addition to supplemented vitamin D, on MS development in individuals with Clinically Isolated Syndrome. We propose that the PhoCIS trial provides a fresh approach to re-defining the reported associations of 25(OH)D levels with MS development and progression.